Inverse Modeling Approach for Evaluation of Kinetic Parameters of a Biofilm Reactor Using Tabu Search. (1st August 2014) - Kumar, B. Shiva; Venkateswarlu, Ch.
ABSTRACT: : The complex nature of biological reactions in biofilm reactors often poses difficulties in analyzing such reactors experimentally. Mathematical models could be very useful for their design and analysis. However, application of biofilm reactor models to practical problems proves somewhat ineffective due to the lack of knowledge of accurate kinetic models and uncertainty in model parameters. In this work, we propose an inverse modeling approach based on tabu search (TS) to estimate the parameters of kinetic and film thickness models. TS is used to estimate these parameters as a consequence of the validation of the mathematical models of the process with the aid of measured data obtained from an experimental fixed‐bed anaerobic biofilm reactor involving the treatment of pharmaceutical industry wastewater. The results evaluated for different modeling configurations of varying degrees of complexity illustrate the effectiveness of TS for accurate estimation of kinetic and film thickness model parameters of the biofilm process. The results show that the two‐dimensional mathematical model with Edward kinetics (with its optimum parameters as μmax ρ s / Y = 24.57, K s = 1.352 and K I = 102.36) and three‐parameter film thickness expression (with its estimated parameters as a = 0.289×10 −5, b = 1.55×10 −4 and c = 15.2×10 −6 ) better describes the biofilm reactor treating the industry wastewater.